ANALISIS KELAYAKAN INVESTASI AKTIVA TETAP PADA INDUSTRI RUMAH TANGGA MOSHIMOSHI CAKE DI SAMARINDA - Abbas, Fitria (EKONOMIA, 2013)
The domestic industry is basically for profit (profit), to support its business activities, the company needs to think about the investment policies, thus one of the factors that affect customer requirements for products of goods and services as well as provide satisfaction and efficiency are the fixed asset investment.Issues to be discussed is